A gestão pedagógico-colaborativa: uma experiência inaciana - Waldow, Tatiane Ayala (Universidade do Vale do Rio dos Sinos, 2022)
The objective of this Professional Master's thesis in Educational Management was to understand which organizational and participatory characteristics correspond to a pedagogical-collaborative management and how they are articulated several areas in a college of the Jesuit Education Network (RJE). The research was carried out at College Anchieta in Porto Alegre/RS. The methodology chosen for the research was qualitative, using observation of the contexts where academic services and administrative sectors operate, document analysis and a questionnaire directed to managers of the mentioned segments. In the content analysis, the organizational and participatory characteristics and how they were evidenced and articulated in the researched educational environments were highlighted as categories, comparing them with the perspectives of a pedagogical-collaborative management. The main conclusion of the research was that the College presents, in its structure, educators and managers who recognize themselves in their functions as collaborators of an educational mission that is a legacy of the Jesuit tradition, they feel that there are many spaces where they collaborate and contribute to education. From their places of work. However, they realize that they still need greater approximations, dialogue and effective actions so that the levels of collaboration are expanded and with greater adherence by the different institutional actors. In this way, at the conclusion of the research, an intervention is suggested in which the educational community has a formative space, through a seminar or study day, podcast, that favors the construction of new perspectives to the needs of the College and how each one can, with its function and collective work, add to the organizational structure, generating greater spaces for collaboration, organization and effective participation in decision-making.
Keywords: Educação jesuíta; Gestão pedagógico-colaborativa; Organização; Participação; Jesuit education; Pedagogical-collaborative management; Organization; Participation; ACCNPQ::Ciências Humanas::Educação